2 - Les economies africaines doivent-elles avoir peur de la Chine ? - Herman Touo (Identity, Culture and Politics, 2011)
Do African economies have to fear China ? The term ‘Fear’ constitutes for some years as the dominant paradigm through which the rise of China as emerging power in the World is analyzed in various realms. This concept of fear appears like a category endowed with a capacity of ambiguous explanatory. It postulates a sort of universal mistrust towards China. From this universalizing cognitive approach, imperialism emerges as a methodical doubt on the use of this concept whose content seems relative. Africa had to organize and stow itself to the Chinese’ locomotive to the will of its interests. But Africa is itself contaminated by Chinese fears. While carrying the fear and who had never been offered economic support since a century or more, Africa surprised with certain Chinese clichés. China poses like a ‘Big Satan Dragon’ to Africa with its arrival to tap African oil, to pillage and influence of big media and some publications. One can ask whether Chinese strong growth controls/ occupies the geopolitical composition of the continent or is China a threat or opportunity for the African economies? To bring elements of response to the questioning, two hypotheses can be drawn here: 1. Of course China constitutes a threat because of its status of emerging power and whose conquering economy conveys the image of an authoritarian new «grand» doubled with predator’s appetite. 2. There is absolutely no need to be afraid of China because it is a giant whose model of development can be a source of inspiration for the African economies in the framework of a relation of win-win partnership. The stake for Africa is to have the mastery of its relations with China that can be an opportunity for this continent. Our thesis is that China occupies the geopolitical reconstruction of Africa, which creates to a certain extent a conflict of interests with the former western powers. And it can be an opportunity for the African economies, especially if governments assume their own financial responsibilities by improving the way of collecting taxes, the business environment, and the quality of the public expense and by putting an end to the capital outflow, or by requiring the transfer of technology from Chinese partners. This is comprehensible given the fact that all weaknesses of Africa can be corrected by assets of Africa which is in a position to recover its status of strategic stake in the new global political and economic order.